2018
DOI: 10.5539/ibr.v11n8p133
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Implementation of Activity-Based Costing: A Study on Malaysian SMEs

Abstract: Literature has indicated that factors such as--the external environment, cost saving mechanisms, user attitude and company size--may have an effect on the implementation of activity-based costing (ABC). Furthermore, literature has revealed that there is still lack of research on the effect of these factors on the implementation of ABC among small and medium sized enterprises (SMEs) in Malaysia. As such the aim of this research is to test the relationships of these factors on the implementation of ABC among SME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 26 publications
3
7
0
2
Order By: Relevance
“…From a study of South African manufacturing SMEs, Msomi et al (2019) concluded that the size of the firm influenced the adoption of MAPs. This accords with the findings of Prihastiwi and Sholihin (2018), Nair and Tan (2018), Ahmad and Mohamed (2015), Albu and Albu (2012), and Holmes and Nicholls (1989). Within SMEs, larger SMEs employ more MAPs than smaller SMEs, owing to the increased complexity of their business (Lopez & Hiebl, 2015).…”
Section: Organization Size and Mapssupporting
confidence: 87%
See 3 more Smart Citations
“…From a study of South African manufacturing SMEs, Msomi et al (2019) concluded that the size of the firm influenced the adoption of MAPs. This accords with the findings of Prihastiwi and Sholihin (2018), Nair and Tan (2018), Ahmad and Mohamed (2015), Albu and Albu (2012), and Holmes and Nicholls (1989). Within SMEs, larger SMEs employ more MAPs than smaller SMEs, owing to the increased complexity of their business (Lopez & Hiebl, 2015).…”
Section: Organization Size and Mapssupporting
confidence: 87%
“…As a result of insufficient training to adopt sophisticated MAPs, accounting staff lack knowledge and skills, resulting in a decreased use of MAPs. However, Nair and Tan (2018) found no significant relationship between the level of accounting staff's qualification and the use of MAPs in Malaysia. This implies that the widespread use of MAPs in medium-sized businesses is not contingent on the presence of qualified accountants.…”
Section: Qualification Level Of Accounting Staff and Mapsmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior literature on the impact of IT on ABC implementation is conflicting (Krumwiede 1998;Nair & Tan 2018). For some organisations adopting ABC, high-quality information systems are considered a key factor in reaching the highest implementation stage where ABC is used extensively and integrated with the primary financial system.…”
Section: Information Technologymentioning
confidence: 99%